Aluminum nanotripods for light-matter coupling robust to nanoemitter orientation - Pacheco-Peña, Víctor (2018)
Nanoantennas enable the concentration and manipulation of light at the (sub‐)nanoscale. This ability offers novel strategies to strengthen light‐matter interactions in a controlled fashion. However, most nanoantennas are highly sensitive to light polarization and emitter orientation, which is disadvantageous for many applications (e.g., Raman and fluorescence spectroscopy depend strongly on molecular symmetry and orientation, as well as on the local optical field gradient). It is also unfortunate that analytical descriptions, essential to bridge experimental observations to knowledge and future design guidelines, have lagged behind. Here, resorting to conformal transformation, aluminum nanotripods excited by a nanoemitter of arbitrary orientation are studied analytically. Our results, corroborated with full‐wave simulations, show that aluminum nanotripods are robust not only to emitter orientation, but also to its position. Hence, this work exemplifies the effectiveness and efficiency of transformation optics to analytically describe and optimize light‐matter interaction in complex plasmonic nanoantennas.